-(x+6-5y)=(x-4+8)

Simple and best practice solution for -(x+6-5y)=(x-4+8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(x+6-5y)=(x-4+8) equation:


Simplifying
-1(x + 6 + -5y) = (x + -4 + 8)

Reorder the terms:
-1(6 + x + -5y) = (x + -4 + 8)
(6 * -1 + x * -1 + -5y * -1) = (x + -4 + 8)
(-6 + -1x + 5y) = (x + -4 + 8)

Reorder the terms:
-6 + -1x + 5y = (-4 + 8 + x)

Combine like terms: -4 + 8 = 4
-6 + -1x + 5y = (4 + x)

Remove parenthesis around (4 + x)
-6 + -1x + 5y = 4 + x

Solving
-6 + -1x + 5y = 4 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
-6 + -1x + -1x + 5y = 4 + x + -1x

Combine like terms: -1x + -1x = -2x
-6 + -2x + 5y = 4 + x + -1x

Combine like terms: x + -1x = 0
-6 + -2x + 5y = 4 + 0
-6 + -2x + 5y = 4

Add '6' to each side of the equation.
-6 + -2x + 6 + 5y = 4 + 6

Reorder the terms:
-6 + 6 + -2x + 5y = 4 + 6

Combine like terms: -6 + 6 = 0
0 + -2x + 5y = 4 + 6
-2x + 5y = 4 + 6

Combine like terms: 4 + 6 = 10
-2x + 5y = 10

Add '-5y' to each side of the equation.
-2x + 5y + -5y = 10 + -5y

Combine like terms: 5y + -5y = 0
-2x + 0 = 10 + -5y
-2x = 10 + -5y

Divide each side by '-2'.
x = -5 + 2.5y

Simplifying
x = -5 + 2.5y

See similar equations:

| 2(2x+3)3(5x+4)= | | (0.25*X)+X=3665.00 | | 6-2z=18-3z | | -3/4w=15 | | f*4+5=11 | | .25x=1567.50 | | (a+3)(a+3)=0 | | 3cos^2(x)-5cos(x)=2 | | -u/u^2 | | x-7(2x-3)=2(5x-2)-3(4x+9) | | (36y^2)-5=y-18y^2 | | -2+3(x-4)=3x-9(x-3)-1 | | 7(x-8)+9=5(x-7) | | 4x-2y=800 | | 5x+3-1*2=54 | | 7(x+6)+x=4(4x+4)+6 | | 2a+7=25+8 | | .417/.875 | | 3x-2(3x-2)=6-(3x-8)+9x | | 7(x-3)+x=2(x+5)+2 | | X^2+x-2=x^3 | | 5/12/7/8 | | (-4+7i)(1+i)= | | 4(2x+5)-(8x+5)=15 | | (3x^4)/(6)=x^6/30 | | 12x/15x | | -(6-3*6)-5=-2*6-2*6+1solve | | X^7=x^4+65 | | .2(4z-10)=.8z-2 | | 1/5(4z-10=4/5z-2 | | (2-v)(2v-3)=0 | | -4(x-4)+5=6(x+4)+1 |

Equations solver categories